Drama of a Nation : Public Theater in Renaissance England and Spain - Cohen, Walter (Cornell University Press, 2019)
During the sixteenth and seventeenth centuries, in the midst of an international florescence of drama, the English and Spanish theaters displayed striking and unique similarities. Although these two national theaters developed in relative isolation from each other, in both countries the plays synthesized native popular traditions and neoclassical learned conventions, a synthesis found neither in the more elite Italian and French drama of the time nor in any other European drama before or since. In Drama of a Nation, Walter Cohen illuminates the causes of this significant parallel development.Working from a Marxist perspective, Cohen seeks to establish correlations among individual plays, dramatic genres, theatrical institutions, cultural milieus, and political and economic systems. He argues that the drama owed its distinctiveness to the public theaters, especially of London and Madrid, which opened in the 1570s and closed, under government order, seventy years later. Both drama and theater in turn depended on a relative cultural homogeneity perpetuated by a state that primarily served the aristocracy. Absolutism, he maintains, first fostered and then undermined the public theater.